FeCl3-catalysed C-N coupling reaction between cyclic ethers and heterocyclic amines - Mani, Suresh; Mohamed, Mashood Ahamed Fazul; Karakkakal, Abdul Khader; Khan, Syed Ali Padusha Mohamed (European Journal of Chemistry, 2014)
A series of 2-hydroxypyrrolidine/piperidine derivatives (4a-h)/(4i-m) were prepared by reacting 2,3-dihydrofuran (2a)/3,4-dihydro-2H-pyran (2b) with various heterocyclic amines (3a-h), using FeCl3.6H2O as catalyst. The synthesized compounds were characterized by various physic chemical techniques such as elemental analysis and spectral analysis viz, 1H NMR, 13C NMR and Mass.